Location optimization of municipal solid waste considering health, safety, environmental, and economic factors - Azadeh, Ali (2018)
Selecting appropriate sites for municipal solid waste (MSW) is a challenging problem for urban communities and has economic and environmental implications. This paper proposes a mathematical optimization model to solve the location problem of MSW sites incorporating both push and pull characteristics. Four objective functions comprising health, safety, environmental (HSE), and economic indicators are considered. These objectives are combined into a single objective function using the weighted sum method and the best method is selected based on noise analysis. The parameter uncertainty is incorporated into the model using expert judgments followed by sensitivity analysis to show the effect of the most important parameters. Using the data from a network of 360 population centers in Tehran, the solution for the model is demonstrated. To our knowledge, this is the first study on location optimization of MSW considering combined HSE and economic indicators. The proposed approach is flexible and parsimonious.